ANALYSING THE CAUSAL RELATIONSHIP AMONG CO2 EMISSION, ENERGY CONSUMPTION AND ECONOMICS GROWTH - Rummana Zaheer, Syed Rashid Ali, Afshan aleem, Syed Aqeel Ahmed (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The study analysis the relationship among CO2 emission, Energy consumption, and economic growth in Pakistan. The annual time series data from 1973 to 2017 used. Both formal and informal method are used to determine the stationary level. For regression analysis, Vector Auto regression (VAR) model is used. The results confirm that theCO2 emission and energy consumption has positive but insignificant effect onper capita GDP or Economic growth. Granger Causality VAR confirms unidirectional causality between Energy consumption and CO2 emission. While no causality found between CO2emission on economic growth and energy consumption on economic growth.